Bacterial Killing by Dry Metallic Copper Surfaces - Santo, Christophe Espírito (American Society for Microbiology (ASM), 2011)
Metallic copper surfaces rapidly and efficiently kill bacteria. Cells exposed to copper surfaces accumulated large amounts of copper ions, and this copper uptake was faster from dry copper than from moist copper. Cells suffered extensive membrane damage within minutes of exposure to dry copper. Further, cells removed from copper showed loss of cell integrity. Acute contact with metallic copper surfaces did not result in increased mutation rates or DNA lesions. These findings are important first steps for revealing the molecular sensitive targets in cells lethally challenged by exposure to copper surfaces and provide a scientific explanation for the use of copper surfaces as antimicrobial agents for supporting public hygiene.